Availability, Affordability, Access, and Pricing of Anti-cancer Medicines in Low- and Middle-Income Countries: A Systematic Review of Literature - Ocran Mattila, Phyllis; Ahmad, Rabbiya; Hasan, Syed Shahzad; Babar, Zaheer-Ud-Din (Frontiers in Public Health, 2021)
Background: Cancer is the second leading cause of death globally accounting for more than half of deaths in Low- and Middle-Income Countries (LMICs). Cancer treatment is expensive and the high prices of cancer medicines have a huge impact on access in LMICs. Scarcity of pricing or affordability data is one of the major barriers in the development of effective and transparent pricing policies in LMICs. This study aimed to conduct a systematic review of the literature regarding pricing, availability, affordability, and access to anti-cancer medicines in LMICs. Method: A systematic search was conducted across six electronic databases: PubMed, Medline/CINAHL (EBSCO), Web of Science, Springer Links, Scopus, and Google Scholar. The literature (from 2015 to 2020) was reviewed to identify original research articles published in English. Results: A total of 13 studies were included in the review with some having multiple outcomes: five studies on pricing, four studies addressed affordability, five studies reported on availability, and four studies on access to anti-cancer medicines. The studies showed that in LMICs, there are wide variations in cancer prices and availability amongst the medicine brands and across different countries, with less affordability by patients with low-income levels, sometimes leading to treatment abandonment. Conclusion: Given the importance of medicine availability and prices in patient access and medicine buying capacity of governments, multi-pronged policy and program approaches by multiple stakeholders are needed to ensure access to cancer medicines.